Rooming-in For Babies Born by Caesarean Section in Dr. Cipto Mangnnkusumo General Hospital Jakarta - Rulina Suradi (Indonesian Pediatric Society, 1988)
Rooming-in was started in our hospital in 1981 for newborns born normally. After having good results with this in mid 1984 we started rooming-in for babies delivered by caesarean section if they fulfilled a certain criteria. But the facilities for rooming-in for caesaren babies were still limited, so not every baby who fulfilled the criteria could be roomed in with the mother. In the year 1986, 4112 babies were born in our hospital among which 868 were delivered by caesarean section. Of the 868 babies 435 babies fulfilled the criteria but only 269 babies could be roomed in with the mother while 166 babies had to be nursed separately. We compared the data of the rooming-in babies to the babies nursed separately. The study showed that in the rooming-in group more mothers were fully breastfeeding on discharge and incidence of sepsis, enteritis and hyperbilirubinaemia were significantly lower while mortality and the incidence of pneumonia, omfalitis, conjunctivitis and pyodermia did not differ significantly.